Skrining Fitokimia Ekstrak Metanol Buah Labu Siam - Maulidina, Freshilla; Parbuntari, Hesty (Periodic, 2023)
Sechium edule. or chayote is a plant that belongs to the Cucurbitaceae family. Almost all parts of this plant can be consumed, one of which is the fruits. chayote can be cooked as a vegetable and is a good source of vitamin C . In this study, phytochemical screening was performed to identify secondary metabolites containing in Musa x paradisiaca L. The results of phytochemical screening showed that Sechium edule. contained secondary metabolites of flavonoids, steroids and saponins, but did not contain alkaloids and terpenoids.